Dampak Pembangunan Perumahan Graha Candi Golf di Kota Semarang - Iswahyudi Anton Setiawan; Bitta Pigawati (Jurusan Perencanaan Wilayah dan Kota, 2018)
Semarang as the capital of Central Java is a metropolitan city whose population continue to grow so that the needed land for activity also increases. One of the problem occurred in rapidly growing urban areas is the demand for human settlement with well-maintained environmental conditions compatible with their allocation and sustainable. Graha Candi Golf elite and semi cluster residential area located in Semarang. The development process of Graha Candi Golf residential is now expanding and equipped with adequate facilities. The purpose of this study is reviewing the Impact of Housing Development of Graha Candi Golf using descriptive method with a spatial approach. The result of this research shows that there are direct positive impacts on the community related to the physical condition of the environment, such as the accessibility. At the sametime the development of Graha Candi Golf also has negative impacts, the decreasing of clean water availability and the quality of water sources. Another benefit that can be felt by the public is the increase of job opportunities to increase family income.